2022
DOI: 10.1177/09544089211073027
|View full text |Cite
|
Sign up to set email alerts
|

Advances in joining technologies for the innovation of 21st century lightweight aluminium-CFRP hybrid structures

Abstract: In the twenty-first century, the application of carbon fiber reinforced polymer (CFRP) materials in the vehicle industry are growing rapidly due to lightweight, high specific strength, and elasticity. In the automobile and aerospace industries, CFRP needs to be joined with metals to build complete structures. The demand for hybrid structures has prompted research into the combination of CFRP and metals in manufacturing. Aluminium and CFRP structures combine the mechanical properties of aluminium with the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…They also investigated various joining methods for obtaining hybrid joints between carbon-fiber-reinforced polymer and aluminum alloys. 27 From the existing literature, it was observed that the FSW of different polymer nanocomposites has been reported by earlier researchers. However, there is a significant research gap for FSW of PP/EPDM/Clay nanocomposites.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…They also investigated various joining methods for obtaining hybrid joints between carbon-fiber-reinforced polymer and aluminum alloys. 27 From the existing literature, it was observed that the FSW of different polymer nanocomposites has been reported by earlier researchers. However, there is a significant research gap for FSW of PP/EPDM/Clay nanocomposites.…”
Section: Introductionmentioning
confidence: 75%
“…They also investigated various joining methods for obtaining hybrid joints between carbon-fiber-reinforced polymer and aluminum alloys. 27…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, connecting CFRTP to metals and maximizing joint performance is a critical issue that has to be faced. For example, CFRTP/aluminum alloy and CFRTP/titanium alloy connection structures are usually used for wing panels, fairings, space optical benches, helicopter blades, ship hulls, and engine cowls 8 . The joints of these structures become the weakest part of the whole structural member, and the quality of the joint directly determines the fatigue strength and service life of the member.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed critical review of the FSW of metals and polymers is discussed in the authors' previous article. 14,15 From the literature, it is understood that past research focussed on feasibility studies and insights of bonding mechanisms during the joining of dissimilar materials. In the meantime, few studies explored the application of ML approaches and statistical optimization techniques for the process design of hybrid polymer and metal hybrid joints.…”
Section: Introductionmentioning
confidence: 99%